Metabolism studies of 4′Cl‐CUMYL‐PINACA, 4′F‐CUMYL‐5F‐PINACA and 4′F‐CUMYL‐5F‐PICA using human hepatocytes and LC‐QTOF‐MS analysis. Issue 3 (3rd January 2023) - Stalberga, Darta; Ingvarsson, Sarah; Bessa, Ghidaa; Maas, Lisa; Vikingsson, Svante; Persson, Mattias; Norman, Caitlyn; Gréen, Henrik
Abstract: 4′Cl‐cumyl‐PINACA (SGT‐157), 4′F‐cumyl‐5F‐PINACA (4F‐cumyl‐5F‐PINACA, SGT‐65) and 4′F‐cumyl‐5F‐PICA (4F‐cumyl‐5F‐PICA, SGT‐64) are a series of new halogenated cumyl synthetic cannabinoid receptor agonists (SCRAs). Due to rapid metabolism, monitoring and screening for SCRAs in biological matrices requires identification of their metabolites. It is an essential tool for estimating their spread and fluctuations in the global illicit market. The purpose of this study was to identify human biotransformations of 4′Cl‐cumyl‐PINACA, 4′F‐cumyl‐5F‐PINACA and 4′F‐cumyl‐5F‐PICA in vitro and characterize for the first time the metabolic pathways of halogenated cumyl SCRAs. 4′Cl‐cumyl‐PINACA, 4′F‐cumyl‐5F‐PINACA and 4′F‐cumyl‐5F‐PICA were incubated with human hepatocytes in duplicates for 0, 1, 3 and 5 h. The supernatants were analysed in data‐dependent acquisition on a UHPLC‐QToF‐MS, and the potential metabolites were tentatively identified. A total of 11 metabolites were detected for 4′Cl‐cumyl‐PINACA, 21 for 4′F‐cumyl‐5F‐PINACA and 10 for 4′F‐cumyl‐5F‐PICA. The main biotransformations were oxidative defluorination, followed by hydroxylation with dehydrogenation, N‐dealkylation, dihydrodiol formation and glucuronidation. Hydroxylations were most common at the tail moieties with higher abundancy for indole than indazole compounds. N‐dealkylations were more common for fluorinated tail chain compounds than the non‐fluorinated 4′Cl‐cumyl‐PINACA. In conclusion, many metabolites retained halogen groups at the cumyl moieties which, in various combinations, may be suitable as analytical biomarkers.